Escherichia coli combination with PD-1 blockade synergistically enhances immunotherapy in glioblastoma multiforme by regulating the immune cells - Guochen Li; Haiyan Yang; Tengfei Ke; Na Tan; Xiaolan Du; Xirui Duan; Xinyan Zhou; Guangrong Zheng; Chengde Liao (Journal of Translational Medicine)
Abstract Background Glioblastoma multiforme (GBM) is the most common and aggressive primary intracranial malignancy. It is characterized by insufficient infiltration of anti-tumor T lymphocytes within the tumor microenvironment (TME), rendering it an “immune cold” disease. This immune deficiency results in poor responses to immune checkpoint blockade (ICB) therapies. Recent studies have demonstrated that bacteria can proliferate within tumors and activate immune responses. Therefore, in this study, we employed Escherichia coli (E. coli) in combination with anti-PD-1 antibodies to treat GBM, with the aim of exploring the immune-activating potential of E. coli in GBM and its synergistic effect on anti-PD-1 therapy. Methods The E. coli and anti-PD-1 antibody therapy were administered intravenously and intraperitoneally, respectively. Complete blood cell count, blood biochemical analysis, hematoxylin and eosin (H&E) staining, and agar plate culture were employed to evaluate the biosafety and tumor-targeting capability of E. coli. ELISA kits were used to detect innate immune cytokines. Flow cytometry and immunofluorescence staining were used to investigate T cells. Tumor volume of tumor-bearing mice was recorded to evaluate the combined treatment efficacy. H&E staining and immunofluorescence staining were used to observe the tumor inhibition markers. Results E.coli can specifically target into the tumor region, and activate the innate immune response in mice. Immunofluorescence staining and flow cytometry results demonstrated that the combination treatment group exhibited a significant upregulation of cytotoxic CD8+ T cells and a marked suppression of regulatory T cells compared to the control group. The expression of Ki67 was significantly downregulated, and TUNEL staining revealed an increased number of apoptotic cells in the combination treatment group. Furthermore, the tumor growth rate in the combination treatment group was significantly slower than that in the control group. Conclusions E. coli exhibits potential anti-tumor activity and can activate the innate immune response and further regulate immune cells in the tumor tissues to synergize the effect of anti-PD-1 therapy on GBM, providing new insights to enhance the efficacy of GBM immunotherapy.